Probing the Catalytic Efficiency of Supported Heteropoly Acids for Esterification: Effect of Weak Catalyst Support Interactions - Ali Alsalme; Aliyah A. Alsharif; Hamda Al-Enizi; Mujeeb Khan; Saad G. Alshammari; Mshari A. Alotaibi; Rais Ahmad Khan; Mohammed Rafiq H. Siddiqui (Journal of Chemistry)
Supported heteropoly acids are an interesting class of solid acid catalysts which possess flexible structure and super acidic properties essentially required for the oil-based biodiesel production. In this study, a series of catalysts containing 25 wt.% of heteropolytungstate (HPW) supported on various clays or SiO2 were prepared, and their catalytic efficiency was evaluated for esterification of acetic acid with heptanol. The as-prepared catalysts were characterized by various techniques including FT-IR spectroscopy, thermogravimetric analysis, X-ray diffraction, scanning electron microscopy, and BET. The catalytic efficiency of both bulk and supported HPW catalysts for the esterification activity strongly depends on the type of support and amount of catalyst; the bulk HPW catalyst and the catalyst supported by kaolinite with 25 wt.% of HPW exhibited highest activity. In order to study the effect of temperature on conversion, all the catalysts were subjected to different reaction temperatures. It was revealed that esterification activity of both bulk and supported HPW catalysts strongly depends upon the temperature variations of the reaction. Besides, the effect of leaching of active sites on the catalysts performance for biodiesel production was also evaluated by inductively coupled plasma studies (ICP). The kaolinite-supported catalyst (25% HPW/kaolinite) demonstrated higher amount of leaching which is also confirmed by the significant decrease in its catalytic activity when it is used for the second time. However, the higher activity demonstrated by HPW/kaolinite maybe because of some homogeneous reaction indicating a weak catalyst support interaction (WCSI) resulting in the leaching of the catalyst during the test. Furthermore, the effects of other reaction variables such as catalyst loading and reaction time on the conversion of acetic acid were also studied.